Zakat as an Instrument of Income Redistribution: an Analysis from the Perspective of Islamic Microeconomics - Rizki Mulia Nanda; Nurul Hikmah; Fathin Azzahra; Husnul Mirzal; Ismail Nura (Journal of Management, Economic, and Accounting, 2026)
This article examines the role of zakat as an instrument of income redistribution through the lens of Islamic microeconomics. Drawing on 22 peer-reviewed articles published between 2015 and 2025, selected through a Systematic Literature Review (SLR) methodology, the study identifies three principal mechanisms through which zakat operates: first, it facilitates direct income transfers to mustahik, substantially enhancing their welfare in accordance with the principle of diminishing marginal utility; second, it corrects distributional failures that market mechanisms alone are unable to resolve; and third, it stimulates the purchasing power of lower-income groups, thereby generating a local economic multiplier effect. On the basis of these findings, this article contends that zakat ought to be recognized not merely as a philanthropic obligation, but as an integral component of a just and inclusive economic architecture. Realizing this potential in practice requires the reinforcement of institutional governance and the professional management of zakat collection and distribution.